Numerical Optimization and Map-Based Manipulation With a Quadrupole Electromagnetic Actuated System - Ma, Weicheng; Huan, Zhijie; Xu, Min (Frontiers in Neurorobotics, 2022)
Electromagnetic actuation is a new technique for non-invasive manipulation, which provides wireless and controllable power source for magnetic micro-/nano-particles. This technique shows great potential in the field of precise mechanics, environment protection, and biomedical engineering. In this paper, a new quadrupole electromagnetic actuated system was constructed, which was composed of four electromagnetic coils, each coil being actuated by an independent DC power supplier. The magnetic field distribution in the workspace was obtained through finite element modeling and numerical simulation via COMSOL software, as well as the effect of the current flow through the coil in the field distribution. Moreover, parameters of the electromagnetic system were optimized through parametric modeling analysis. A magnetic field map was constructed for rapidly solving the desired driving current from the required magnetic flux density. Experiments were conducted to manipulate a micro-particle along the desired circular path. The proposed work provides theoretical references and numerical fundamentals for the control of magnetic particle in future.